Baseline characteristics of hypertensive patients with descending thoracic or abdominal aortic aneurysm referred for endovascular treatment - A. P. Gurevich; M. V. Ionov; I. V. Emelianov; A. G. Vanyurkin; Yu. K. Panteleeva; A. V. Chernov; M. A. Chernyavsky; A. O. Konradi (Российский кардиологический журнал, 2024)
Aim. To analyze perioperative characteristics, including central hemodynamic parameters, of patients with hypertension (HTN) and descending thoracic aortic aneurysm (TAA) or abdominal aortic aneurysm (AAA) who were referred for endovascular aortic repair ([T]EVAR).Material and methods. Local registry data were used. The study included 126 patients (103 men, 67±9 years). In addition to the basic examination, noninvasive measurement of central blood pressure (BP) and carotid-femoral pulse wave velocity (cfPWV) was performed. Quality of life (QOL) was assessed using the EQ-5D-3L questionnaire.Results. The most common comorbidities were coronary artery disease (68%), obesity (39%), chronic kidney disease (26%), and type 2 diabetes (18%). Patients with AAA were significantly older and had a higher comorbidity burden, but had a better QOL than patients with TAA (59% vs 71%, p<0,05. High medication adherence was noted in 31% of patients receiving an average of 2 antihypertensive drugs and 59% of them had controlled HTN. Carotid-femoral PWV was higher (10,9 vs 9,6 m/s, p=0,006) and augmentation index (AIx) was lower in TAA (21% vs 29%, p<0,001). Large aneurysm size was associated with lower cfPWV and increased central diastolic BP (p=0,01 and p=0,03, respectively). Increased central pulse pressure (CPP) was positively associated with left ventricular mass index (r=0,21, p=0,037). A decrease in CPP and AIx was observed after [T]EVAR.Conclusion. Patients with HTN and TAA/AAA referred for [T]EVAR have a high comorbidity burden and high QOL. Although the vast majority of patients receive a combination of only two drugs, insufficient adherence to therapy has been revealed. An increase in aneurysm diameter is associated with a decrease in cfPWV and increased central diastolic BP, indicating a potential impact of aneurysm on central hemodynamics in patients receiving antihypertensive therapy.